2019
DOI: 10.1080/21691401.2019.1648278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of synergistic antibacterial effect of silver nanoparticles and ebselen

Abstract: The emerging and spreading of multi-drug resistant (MDR) bacteria have been becoming one of the most severe threats to human health. Enhancing oxidative stress as mimicking immune system was considered as a potential strategy to fight against infection of MDR bacteria. In this study, we investigated the antibacterial efficiency of such a strategy which combines silver nanoparticles (AgNPs) with ebselen. The results showed that AgNPs and ebselen combination had significant synergistic killing effects both on Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…As shown in Figure 3b, both AgNPs and AgNPs−PEI−Ce6 can completely kill the E. coli at the testing concentration, which can be ascribed to the higher sensitivity to the Ag + of the Gram-negative bacteria. 43 However, when the concentration of AgNPs was reduced to 0.005 mg mL −1 (Figure S9), the composite AgNPs−PEI−Ce6 can still eliminate the bacteria, while 10 5 cfu mL −1 of E. coli survived from the treatment of AgNPs, demonstrating the superiority of the combined treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…As shown in Figure 3b, both AgNPs and AgNPs−PEI−Ce6 can completely kill the E. coli at the testing concentration, which can be ascribed to the higher sensitivity to the Ag + of the Gram-negative bacteria. 43 However, when the concentration of AgNPs was reduced to 0.005 mg mL −1 (Figure S9), the composite AgNPs−PEI−Ce6 can still eliminate the bacteria, while 10 5 cfu mL −1 of E. coli survived from the treatment of AgNPs, demonstrating the superiority of the combined treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Similar to silver ions, silver nanoparticles are strong inhibitors of bacterial thioredoxin reductase and have a synergistic effect on E. coli and S. aureus in vitro in combination with ebselen [ 35 ]. The activity of E. coli thioredoxin reductase decreased in a concentration-dependent manner; an 80% inhibitory effect of nanoparticles was observed at a concentration of 0.54 µg/mL.…”
Section: Synergy Of Ebselen With Silvermentioning
confidence: 99%
“…Several studies have shown that application of exogenous natural AMPs can have immunomodulatory and protective effects against infectious keratitis ( Gao and Yu, 2015 ; Kolar et al, 2015 ; Shah et al, 2017 ). Furthermore, it has been observed that AMPs can synergize with each other and additional antibacterial enzymes ( Nagaoka et al, 2000 ; Singh et al, 2000 ; Wu et al, 2009 ; Chen et al, 2019 ). From this, researchers hypothesized that AMPs could synergize with current antibiotic therapies to potentiate bactericidal effects ( Li et al, 2014 ; Carion et al, 2020 ).…”
Section: Therapeutic Use Of Antimicrobial Peptidesmentioning
confidence: 99%